(untitled) (Raparin Journal of Humanities (RJH), 2024)
The recent economic، social and technological developments resulted in the emergence of multiple private large economic and financial institutions or corporations (the "Corporations") that perform a range of activities with significant influence on the society. Indeed، this can bring great benefits to the society if their activities are properly made، while cause severe damage if they corrupt. Hence، the dangers caused by these corporations and the expanding scale of their damage can lead to economic crime، which is far greater than the harm caused by natural persons. Thus، it is no longer acceptable to ignore such crimes، particularly when the civil penalty is no longer appropriate to ignore their deviations on these corporations which brought huge profits to them. This created an advanced jurisprudence calling for the necessity of bringing punitive measures against these corporations in order to prevent and lessen their dangers to the society. The rapid transition from socialism to capitalism in Iraq after 2003 led to a sharp increase in the number and diversified activities and economic openness that controlled the economy، while the criminal jurisprudence was steps behind such fundamental changes. This research aims to demonstrate the importance of designating criminal responsibilities to these corporations to protect the society، and to identify the legal loopholes in Iraq on how to address them. Despite the existence of the principle of “publicity” for economic crimes or not economic crimes، according to the conditions that must be met in order to be take responsibility، under Article (80) of the Penal Code No. 111 of 1969، hitherto this article alone cannot go side-by-side with the dangers created by these corporations، which requires exclusive fundamental amendments، introducing more legislation providing strict punitive measures against these corporations aiming to safeguard the overall economic system.